Pendekatan Teaching at the Right Level dalam Mengatasi Kesenjangan Pemahaman Matematika Peserta Didik - Husna, Fani Rahmawati; Firdaus, Hana Puspita Eka; Indriati, Erlyn (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2024)
Mathematics is a fundamental compulsory subject in various fields of life and technology. However, many students consider mathematics difficult and boring, so many students have difficulty learning. This study aims to overcome the gap in mathematical understanding of class VII C students of SMP Negeri 1 Balung through the Teaching at the Right Level (TaRL) approach and the Problem Based Learning (PBL) learning model. The method used is Classroom Action Research (PTK) with two cycles. Each cycle involves the planning, implementation, observation, and reflection stages. This study was conducted on 31 students with statistical data presentation material. The results showed an increase in the average value from 79.4 in cycle I to 82.7 in cycle II. The increase in the lowest value from 54 to 67 indicated a reduction in the gap in understanding. In addition, the number of students who achieved completeness increased by 12.5%. The TaRL approach combined with PBL is effective in improving learning outcomes and reducing the gap in student abilities. However, this approach requires more preparation by teachers, including grouping students and creating learning materials that are appropriate to the level of student ability. TaRL can also be used to increase student interest, motivation, and learning activity.